AMELIORATIVE POTENTIAL OF ARTEMISIA CAPILLARIS FORMULA ON NONALCOHOLIC FATTY LIVER DISEASE IN RATS THROUGH REGULATION OF FAT METABOLISM - Zhang, Yuchen; Zhao, Jinyan; Zhong, Xiaoyong; Zheng, Haiyin; Li, Ying; Liu, Liya; Wan, Yun; Peng, Jun; Hong, Zhenfeng (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: Artemisia Capillaris Formula (ACF), a traditional Chinese medicinal therapy, has been used clinically in China to treat Nonalcoholic Fatty Liver Disease (NAFLD) for many years. However, the mechanism of action of this treatment on NAFLD is still unknown. The goal of the present study is to test whether Artemisia Capillaris Formula protects against NAFLD through regulation of lipid metabolism. Methods: Rat models of NAFLD were established through consumption of a high-fat diet (HFD) for 8 weeks. 60 rats were randomly divided into 6 groups (10 rats per group): the control (standard diet) group, the model (HFD) group, the polyene phosphatidylcholine treated HFD group, and the ACF-treated HFD groups (high-, medium- and low-dose). During weeks 5−8 of the HFD regimen, drugs were intra-gastrically administrated to selected groups for a total of 4 weeks. Hepatic changes were observed through pathological examination of Hematoxylin and eosin-stained tissues, quantification of lipid metabolites from sera (ALT, AST, ALP activity and TG, TC, HDL-C, LDL-C), and quantification of related gene and protein expression levels by RT-PCR and Western blotting. Results: A high-fat diet promoted obesity and the development of hepatomegaly, hepatosteatosis and dyslipidemia in rats after 8 weeks. Treatment with ACF alleviated hepatosteatosis and also protected against high fat diet-induced dyslipidemia. We found that ACF reduced ALT, AST, ALP, TG, TC, and LDL-C and increased HDL-C levels in sera from treated NAFLD rats. In addition, gene and protein expression levels of FAS and ACC were down-regulated following ACF treatment, whereas expression levels of CPT were up-regulated. Conclusion: ACF ameliorates high-fat diet-induced hepatosteatosis and dyslipidemia in rats by altering lipid metabolism-related gene expression, specifically of FAS, ACC, and CPT.